2014
DOI: 10.1095/biolreprod.114.119560
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism in the Orl Rat Is Associated with Muscle Patterning Defects in the Fetal Gubernaculum and Altered Hormonal Signaling1

Abstract: Cryptorchidism, or undescended testis, is a common male genital anomaly of unclear etiology. Hormonal stimulation of the developing fetal gubernaculum by testicular androgens and insulin-like 3 (INSL3) is required for testicular descent. In studies of the orl fetal rat, one of several reported strains with inherited cryptorchidism, we studied hormone levels, gene expression in intact and hormone-stimulated gubernaculum, and imaging of the developing cremaster muscle facilitated by a tissue clearing protocol to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 46 publications
8
31
0
Order By: Relevance
“…2 We observed that prenatal muscle development is abnormal in the GCC of the cryptorchid LE/orl rat, and although inversion occurs, the GCC is subsequently diverted into the superficial inguinal pouch postnatally. 12 We were, thus, motivated to perform additional prenatal studies to define the cellular properties of the rat GCC that set the stage for normal inversion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 We observed that prenatal muscle development is abnormal in the GCC of the cryptorchid LE/orl rat, and although inversion occurs, the GCC is subsequently diverted into the superficial inguinal pouch postnatally. 12 We were, thus, motivated to perform additional prenatal studies to define the cellular properties of the rat GCC that set the stage for normal inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Care was provided, timed pregnancies generated and euthanasia performed as described previously; 12 the morning of the day of sperm detection was designated embryonic day 0 (E0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations